The Financial Sector : Redefining a Broader Sense of Purpose. - International Monetary Fund. Communications Department (Washington, D.C. : International Monetary Fund, 2019)
IMF Managing Director Christine Lagarde delivered this address at Guildhall as part of the World Traders' Tacitus Lecture series in London on February 28, 2019.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet